Ruwatan Bumi Cipancar: Strategi Pengembangan Pariwisata Budaya Berbasis Kearifan Lokal - Jenal Abidin; Budiarto; Lala Siti Sahara; Rahmat Darmawan (STIE Pariwisata API Yogyakarta, 2025)
This study examines the Ruwatan Bumi tradition in Cipancar Village, Subang Regency, as a potential cultural-based tourism development. Ruwatan Bumi is an annual ritual expressing gratitude for agricultural yields and serves as a platform for integrating local arts such as Debus, Gemyung Jaipong, Sisingaan, and Lengser. This tradition strengthens community identity, social cohesion, and spiritual values. The research employs a descriptive qualitative approach through observation, interviews, and documentation, with interactive analysis based on Miles & Huberman and SWOT analysis. The results indicate that the main strengths lie in the philosophical values and diversity of local arts, while weaknesses include limited digital promotion, absence of a formal management institution, and low involvement of younger generations. Development strategies focus on digital documentation, establishing a management institution, and packaging the tradition into an annual festival integrated with SMEs and local products. Thus, Ruwatan Bumi functions not only as a customary ritual but also as a means of cultural preservation, education, and a driver of sustainable tourism grounded in local wisdom.